An innovative system for promoting cleaner production: mandatory cleaner production audits in China. (1st December 2015) - Bai, Yanying; Yin, Jie; Yuan, Yin; Guo, Yajing; Song, Danna
Abstract: Many studies have shown that positive and negative incentives can greatly promote cooperation in public goods games. The best policy for turning a population of defectors into a population of cooperators is to provide the "carrot" first and the "stick" later. Cleaner production (CP) is a new preventive environmental strategy, and its promotion is also an example of a public goods game. Voluntary participation and other positive incentives have been widely used to encourage industries to implement CP worldwide. However, taking into consideration specific industry characteristics and new environmental management requirements in China, the Chinese Cleaner Production Promotion Law proposes use of mandatory cleaner production audits (as compared to voluntary cleaner production initiatives) as innovative measures for advancing CP. This paper provides a general overview of this innovative system, explaining how the mandatory audit system was established and promoted in various policies, regulations, and national plans, and analyzing the design of the system. The paper also summarizes implementation results of the mandatory cleaner production audit system, based on annual surveys conducted in all provinces of China between 2008 and 2011. The Chinese experience can be used as a reference case by other developing countries similar to China.